The Effectiveness of the Think-Pair-Share (TPS) Learning Model Based on Vocabulary Cards to Improve Arabic Speaking Skills - Hermawan, Ade Rizky; Syarifah, Ainun (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to test the effectiveness of the Think Pair Share (TPS) cooperative learning model combined with vocabulary cards in improving the Arabic speaking skills (maharah kalam) of Madrasah Tsanawiyah students. The background of this study stems from the low speaking ability of students due to limited vocabulary, shyness, and a lack of interactive learning methods. This study uses a quantitative approach with a One Group Pretest-Posttest Design, where the research subjects consist of 38 seventh-grade students at MTsN 1 Lamongan. Data were collected through speaking tests before (pretest) and after (posttest) the learning treatment using the TPS model based on vocabulary cards. Data analysis was performed using descriptive statistics and a paired sample t-test. The results of the study showed a significant increase in the average score from 74.39 on the pretest to 89.58 on the posttest, with a difference of 15.19 points. The t-test yielded a value of -8.736 with a significance level of p = 0.000 (< 0.05), confirming that the difference between the pretest and posttest scores is statistically significant. These findings confirm that the implementation of the TPS model based on vocabulary cards is effective in improving students' speaking skills. Pedagogically, this model not only expands vocabulary mastery but also enhances confidence, oral participation, and fluency in speaking. This study recommends that Arabic language teachers in madrasahs can adopt the TPS with vocabulary cards as an alternative contextual, interactive, and enjoyable learning strategy in developing maharah kalam.